ANALISIS KUALITAS PELAYANAN KESEHATAN IBU HAMIL DAN MELAHIRKAN PADA PUSKESMAS PONED KOTA SEMARANG - Trimas Ayu Lestari; Landjar Kurniawan (Journal of Public Policy and Management Review, 2018)
Implementation of public services is an effort to meet the needs of society undertaken by the government in the implementation of the provisions of legislation. Health services is one of the basic needs services that must be provided, and is the responsibility of the government in an effort to achieve the welfare of the community. The Mortality Rate is one of the measurements of health status in a region, one of the Mortality Rate that can be used as a measure of health is the Maternal Mortality Rate (MMR). AKI Semarang City in 2016 reached 32 deaths, to suppress Maternal Mortality Rate Semarang city participated in implementing Basic Essential Neonatal Obstetric Service (PONED) on maternal health service at 6 Puskesmas. This study aims to determine how the quality of maternal health services at the PONED Semarang Puskesmas to support the suppression of AKI. The method used in this research is a qualitative data analysis approach by conducting research on users of maternal health services at PONED Puskesmas. The results showed the quality of service based on tangible dimension, reliability, responsiveness, assurance, and empathy is good. However, the indicator of the completeness of health care equipment on tangible dimension is still in the bad category which means there is need for improvement.